Etika dan Profesional Humas dalam Lembaga Pendidikan Islam: Studi Kasus di SMP Plus Darus Sholah Jember - Moh. Iqbal Maulana; Mohammad Nafi’ul ’Ulum; Moh. Kholilur Rohman; Muhammad Sofyan Hariyanto; Rofiq Hidayat (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research stems from the urgency of the role of public relations in Islamic educational institutions, particularly madrasas, which is increasingly complex and strategic in the current digital and information era. Public relations is not only tasked with disseminating information but also with building an image, maintaining public trust, and managing effective communication between the madrasa and various stakeholders such as students, parents, teachers, and the wider community. This study aims to identify and analyze the application of ethics and professionalism in public relations at SMP Plus Darus Sholah in Jember and its impact on the institution's image and public trust. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that the application of Islamic ethical values—such as shiddiq (honesty), amanah (trustworthiness), and tabligh (transparency)—in public relations practices significantly enhances the madrasa's credibility and public trust. Additionally, the professionalism of public relations officers, characterized by structured communication planning and interpersonal ethics, plays a crucial role in building a positive institutional image. However, challenges such as a lack of formal training and understanding of ethical standards remain. The implications of this study highlight the need for policy recommendations to enhance the capacity and integrity of public relations personnel in Islamic educational institutions to support their role as the forefront of institutional communication.